Ink-substrate interactions during 3D printing revealed by time-resolved coherent X-ray scattering. (August 2020) - Torres Arango, M.; Zhang, Y.; Zhao, C.; Li, R.; Doerk, G.; Nykypanchuk, D.; Chen-Wiegart, Y-c. K.; Fluerasu, A.; Wiegart, L.
Abstract: Additive printing techniques are regarded as revolutionary and versatile methods of advanced device manufacturing, stemming from the possibility to pattern materials on a custom-based approach and the potential to create novel microstructures and achieve new functionalities. Despite these advantages, the inherent anisotropy of the printing process is a source of property gradients within the printed materials, often associated with variable and/or poor performance. Up to date, the evolutionary pathways associated with printing have largely remained unaddressed, mainly owing to the difficulty to study the transformations induced in the material during processing. Time-resolved coherent X-ray scattering techniques, such as X-ray photon correlation spectroscopy, enable the in situ study of transient nanoscale and mesoscale states in a large variety of materials, including amorphous ones, by directly accessing the most relevant timescales and length scales of their nanoscale and mesoscale dynamics, self-assembly, and mesostructure evolution. We conduct in operando studies of continuous-flow direct writing with colloidal inks, focusing on how the ink formulation and ink-substrate interactions affect the processes that determine the macroscopic properties of the printed materials. We find fundamental differences in the ink structural relaxations emerging from the primary colloid properties (monodisperse versus aggregated colloids) and the substrates surface energy and mechanical properties. Our work helps to reveal and quantify the basic science governing the evolution of 3D-printed materials during processing, ultimately improving engineering criteria for the design of printable materials. Graphical abstract: Ink relaxation dynamics, mesostructure evolution, and ink-substrate interactions in continuous-flow direct ink writing are explored by X-ray photon correlation spectroscopy. Image 1 Highlights: Coherent X-rays reveal structural and dynamic evolution in 3D printed inks. Ink-substrate interactions affect the mesoscale evolution during printing process. Temporal heterogeneities are associated with the formation of structural defects.